Noise Reduction in Ship Engine Room by Optimisation of Muffler Design - Sunarsih Sunarsih; Taufik Fajar Nugroho; Mirfak Yunan Navyazka (International Journal of Marine Engineering Innovation and Research, 2020)
Noise level onboard, particularly in the engine room, requires a careful monitor to not causing any disruption or discomfort to the shipboard environment. For monitoring purposes, an appropriate alternative system can be applied if the noise level exceeds the limit set by applicable regulations such as IMO, ABS, and LR. The current research uses computational methods to map noise contours in the engine room and recommends some muffler models to reduce the noise level in the MV Natuna Express engine room. Based on the field measurement, the noise level exceeds the Standards value at a maximum of 110 dB. Mapping and designing of the muffler models were based on the measurement data. Simulation results show that greater transmission loss hence noise reduction is affected significantly by the expansion of muffler chamber length and diameter. Modification of the muffler chamber using plywood and the tailpipe on both ME ON Generator ON and ME OFF Generator ON conditions respectively reduce the noise approximately by 24.94 dB and 10.50 dB.